AODTU-004 Endoscopic submucosal dissection for colorectal neoplasia: the experience of a uk tertiary referral centre. (17th June 2017) - Emmanuel, A; Gulati, S; Burt, M; Hayee, B; Haji, A
Abstract : Introduction: Despite the advantages of endoscopic submucosal resection (ESD) demonstrated in large series from the far east, the procedure is not commonly practiced in the west and its role in standard practice is still debated. Although limited evidence regarding its efficacy in European practice is emerging, few centres in the United Kingdom perform ESD regularly, if at all. We report the experience of a UK tertiary referral institution using ESD as part of a lesion specific, pragmatic approach to endoscopic resection in a complex patient cohort. Method: Patients who underwent ESD of colorectal lesions were included. Lesions were assessed with magnification chromoendoscopy, supplemented by colonoscopic ultrasound. to determine morphology, pit pattern, risk of submucosal invasion, and presence of submucosal fibrosis or scarring. ESD was used where en bloc resection was deemed essential, or as part of a hybrid procedure to ensure resection of a dominant nodule or suspicious area of a lesion in one piece, or where fibrosis or scarring would make standard EMR impossible. A resection was designated a hybrid procedure if ESD was used to effect mucosal incision and submucosal dissection to assist subsequent snare resection. Results: 438 colorectal lesions were resected. ESD was used in 97 cases, 49 cases used ESD alone and 48 as part of a hybrid procedure. 74% had 1 or more failed attempts at resection or significant manipulation in the form of ≥6 or more biopsies or tattoo into the lesion prior to referral to our institution. Only 8 of the remaining patients had no prior biopsies performed. The mean lesion size was 63 mm. En bloc resection was achieved in 89.8% where ESD was used alone, with a recurrence rate of 5.3% after a mean follow up of 13.3 months. There were 6 microperforations treated with either endoscopic clips or antibiotics alone with no adverse sequelae, and one clinically significant perforation requiring surgery. However, the lesion in this case contained an adenocarcinoma with deep submucosal invasion. There was no residual tumour in the surgical resection specimen. Post-procedure bleeding occurred in 6 patients, none of whom required additional interventional therapy. 71% of cases were successfully performed as day case procedures. 97% of patients without invasive cancer were free from recurrence and had avoided surgery at last follow up. Conclusion: ESD can be safely and effectively incorporated into European practice as an essential adjunct in the treatment of a particularly complex patient cohort. As a result of large lesion size and very high rates of previous significant manipulation of lesions by the time of referral, a pragmatic, lesion-specific approach in choosing the resection technique is recommended. Disclosure of Interest: None Declared